Checklist of digenean parasites of wild mammals from Argentina - Lunaschi, Lía I.; Drago, Fabiana B. (Zootaxa, 2007)
A summary of the literature on the digeneans of wild mammals in Argentina is presented. This is the first compilation of 51 parasitological papers published from 1909 to present. This review includes 26 native species and two introduced species (1 Artiodactyla, 6 Carnivora, 6 Cetacea, 3 Chiroptera, 2 Didelphimorphia, 1 Primate, 8 Rodentia and 1 Lagomorpha) and contains 42 species of adult digeneans belonging to 32 genera and 18 families, of which 9 species (21%) were recorded as new species. The present review provides data on hosts, geographical distribution, site of infection, life cycle, the location of material deposited in Helminthological Collections and references for the parasite species arranged by families. A host/parasite list is also provided. In addition, Gymnoacetabulum n g. is proposed to replaced the genus Suttonia Lunaschi, 2002 (Lecithodendriidae) from bats, which is preoccupied by Suttonia Smith, 1953 (Perciformes, Serranidae).